Rapid assessments in urban areas: lessons from Bangladesh and Tanzania - Garrett, James L.; Downen, Jeanne (International Food Policy Research Institute, 2001)
The diversity of urban areas presents substantial challenges to the validity of information from rapid assessments, yet CARE’s experiences in Bangladesh and Tanzania suggest a number of ways that rapid assessment procedures can be strengthened to address these concerns.